Child health, parental well-being, and the social safety net - Achyuta Adhvaryu; N. Meltem Daysal; Herdis Steingrimsdottir; Teresa Molina Millán; Herdis Steingrimsdottir (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2023)
How do parents contend with threats to the health and survival of their children? Can the social safety net mitigate negative economic effects through transfers to affected families? We study these questions by combining the universe of cancer diagnoses among Danish children with register data for affected and matched unaffected families. Parental income declines substantially for 3-4 years following a child's cancer diagnosis. Fathers' incomes recover fully, but mothers' incomes remain 3% lower 12 years after diagnosis. Using a policy reform that introduced variation in the generosity of targeted safety net transfers to affected families, we show that such transfers play a crucial role in smoothing income for these households and, importantly, do not generate work disincentive effects. The pattern of results is most consistent with the idea that parents' preferences to personally provide care for their children during the critical years following a severe health shock drive changes in labor supply and income. Mental health and fertility effects are also observed but are likely not mediators for impacts on economic outcomes.
Keywords: I10; J13; J22; 330; child health; income; labor supply; safety net; cash transfers; disincentive effects; long-run effects; mental health; childhood cancers; Denmark